The principles of flight for pilots - Swatton, P. J. (Aerospace series, 2011)
An accessible, clearly organized study guide for student pilots wishing to take commercial ground examinations to obtain ATPL or CPL licenses, this book also provides a reliable up-to-date reference for qualified and experienced personnel wishing to improve their understanding of the principles of flight.